MATHEMATICS LEARNING MANAGEMENT WITH THE INTEGRATION OF RESPONSIBLE CHARACTER VALUE: A CASE STUDY AT SMA MUHAMMADIYAH 1 SURAKARTA - Siti Lestari; Endang Fauziati (Universitas Muhammadiyah Semarang, 2021)
This research has objective of describing (1) learning planning (2) learning implementation and (3) mathematics learning evaluation at SMA Muhammadiyah 1 Surakarta with the integration of responsible character value. Subject of the research are principal, mathematics teacher and students of SMA Muhammadiyah 1 Surakarta. This research is qualitative research. Data collection technique for lesson plan is gained from syllabus and lesson plan (RPP) as well as documentation. Meanwhile data collection technique for implementation information and learning evaluation is used observation and interview. Qualitative data technique analysis used is interactive model. The findings of the research showed that (1) mathematics learning planning with the integration of responsible character value is implemented vary by the teachers, (2) the implementation of mathematics learning with the integration of responsible character has not fully implemented by the teachers, and (3) evaluation of mathematics learning with the integration of responsible character has not fully implemented by the teachers. From those points, it can be concluded that mathematics learning with the integration of responsible character has not fully implemented by the teachers toward students at SMA Muhammadiyah 1 Surakarta. Keywords: management, Mathematics learning, responsible character